The Neoepitopes on Methylglyoxal- (MG-) Glycated Fibrinogen Generate Autoimmune Response: Its Role in Diabetes, Atherosclerosis, and Diabetic Atherosclerosis Subjects. (21st December 2021) - Rehman, Shahnawaz; Song, Jiantao; Faisal, Mohammad; Alatar, Abdulrahman A.; Akhter, Firoz; Ahmad, Saheem; Hu, Bo
Abstract : Objectives . In diabetes mellitus, hyperglycemia-mediated nonenzymatic glycosylation of fibrinogen protein plays a crucial role in the pathogenesis of micro- and macrovascular complications especially atherosclerosis via the generation of advanced glycation end products (AGEs). Methylglyoxal (MG) induces glycation of fibrinogen, resulting in structural alterations that lead to autoimmune response via the generation of neoepitopes on protein molecules. The present study was designed to probe the prevalence of autoantibodies against MG-glycated fibrinogen (MG-Fib) in type 2 diabetes mellitus (T2DM), atherosclerosis (ATH), and diabetic atherosclerosis (T2DM-ATH) patients. Design and Methods . The binding affinity of autoantibodies in patients' sera (T2DM, n = 100 ; ATH, n = 100 ; and T2DM-ATH, n = 100 ) and isolated immunoglobulin G (IgG) against native fibrinogen (N-Fib) and MG-Fib to healthy subjects (HS, n = 50 ) was accessed by direct binding ELISA. The results of direct binding were further validated by competitive/inhibition ELISA. Moreover, AGE detection, ketoamines, protein carbonyls, hydroxymethylfurfural (HMF), thiobarbituric acid reactive substances (TBARS), and carboxymethyllysine (CML) concentrations in patients' sera were also determined. Furthermore, free lysine and free arginine residues were also estimated. Results . The high binding affinity was observed in 54% of T2DM, 33% of ATH, and 65% of T2DM-ATH patients' samples with respect to healthy subjects against MG-Fib antigen in comparison to N-Fib (p < 0.05 to p < 0.0001 ). HS sera showed nonsignificant binding (p > 0.05 ) with N-Fib and MG-Fib. Other biochemical parameters were also found to be significant (p < 0.05 ) in the patient groups with respect to the HS group. Conclusions . These findings in the future might pave a way to authenticate fibrinogen as a biomarker for the early detection of diabetes-associated micro- and macrovascular complications.